Imaging, Manipulation, and Analysis of Biomolecules, Cells, and Tissues XVII 2019
DOI: 10.1117/12.2507505
|View full text |Cite
|
Sign up to set email alerts
|

Cellular refractive index comparison of various prostate cancer and noncancerous cell lines via photonic-crystal biosensor

Abstract: The current clinical standard for mass screening of prostate cancer are prostate-specific antigen (PSA) biomarker assays. Unfortunately, the low specificity of PSA's bioassays to prostate cancer leads to high false-positive rates, as such there is an urgent need for the development of a more specific detection system independent of PSA levels. In our previous research, we have successfully demonstrated, with the use of our Photonic-Crystal based biosensor in a Total-Internal-Reflection (PC-TIR) configuration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Recent research is directed towards sensing the changes linked to tumor advancement within tissues and their microenvironment, aiming to facilitate the early-stage tumor detection [6][7][8][9][10][11] . Tumor progression induces stiffening of the tissue and increased disorder due to fibrosis, causing alterations in biomechanical properties, local refractive index, viscoelasticity, and surface roughness of cancerous tissues [12][13][14] . These changes will alter the scattering conditions in the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research is directed towards sensing the changes linked to tumor advancement within tissues and their microenvironment, aiming to facilitate the early-stage tumor detection [6][7][8][9][10][11] . Tumor progression induces stiffening of the tissue and increased disorder due to fibrosis, causing alterations in biomechanical properties, local refractive index, viscoelasticity, and surface roughness of cancerous tissues [12][13][14] . These changes will alter the scattering conditions in the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, several techniques are being developed to study the morphological, biochemical, and biomechanical changes in tumor regions and their microenvironments [21][22][23][24][25]. It has been found that tumor progression causes changes in the local refractive index, biomechanical properties, surface roughness, and viscoelasticity of the tissues [26][27][28]. Changes in these properties will modify the scattering scenario and thus can be detected using random lasing.…”
Section: Introductionmentioning
confidence: 99%
“…As the protein expression changes when the cells undergo EMT, we believe these biochemical changes can be correlated to changes in refractive index of the cell membrane. We have previously demonstrated the ability to use cellular membrane RI, as a novel contrast parameter to allow for label-free detection of prostate cancer cells [9][10][11] In this paper, we report a novel method to characterize prostate cancer cells undergoing EMT based on the cell's membrane RI via the use of a label-free biosensing system constructed with a Photonic Crystal Biosensor in a TotalInternal Reflection (PC-TIR) configuration. EMT in prostate cells lines was induced by treating the cells with Transforming Growth Factor Beta 1 (TGF-β1).…”
Section: Introductionmentioning
confidence: 99%